Symposium 8: About PebblePad - Sutherland, Shane (Proceedings of the International Conference on Networked Learning, 2008)
ePortfolios are purposeful collections of digital items presented to distributed audiences to present a view of the portfolio author commensurate with the perceived, or articulated, expectation of that audience. Increased eportfolio activity in the UK was largely driven by Personal Development Planning and is, more recently, being driven within and beyond Higher Education by Continuing Professional Development and Professional (Re)Accreditation. Developing an understanding of the needs of eportfolio users, by reference to prior learning technology experience and direct user involvement, was an essential aspect of the design process which led to the creation and subsequent implementation of PebblePad which is now the most widely used eportfolio/personal learning system in UK HE. The design, development and implementation stages PebblePad's evolution are discussed herein along with an exploration of a single system is able to be used by teachers and students alike for myriad purposes. It is the versatility of the system that led to its selection by the JISC-funded 'Flourish' project focussing upon staff use of an eportfolio to support their personal e-administration.